2022
DOI: 10.3390/su142013609
|View full text |Cite
|
Sign up to set email alerts
|

The Carbon Emissions Effect of China’s OFDI on Countries along the “Belt and Road”

Abstract: With the continuous practice of the “Belt and Road” initiative, the countries along the “Belt and Road” have achieved rapid social and economic development. However, environmental problems have become increasingly prominent. Around the world, there are comments that China’s “Belt and Road” initiative is a result of resource plundering, transfer of backward production capacity, and environmental degradation of countries along the line. This study quantitatively evaluated the static, dynamic, linear, and non-lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…Therefore, our research question is as follows: Does China's OFDI reduce the environmental performance of BRI countries? Due to large differences in research methods and sample data, the existing literature exploring whether there is a definite relationship between China's OFDI and environmental performance in BRI countries has not yet reached a conclusion [5,10,11]. In addition, we found that most of the existing literature uses a single environmental proxy variable from a partial perspective, instead of comprehensive environmental performance.…”
Section: Introductionmentioning
confidence: 80%
See 4 more Smart Citations
“…Therefore, our research question is as follows: Does China's OFDI reduce the environmental performance of BRI countries? Due to large differences in research methods and sample data, the existing literature exploring whether there is a definite relationship between China's OFDI and environmental performance in BRI countries has not yet reached a conclusion [5,10,11]. In addition, we found that most of the existing literature uses a single environmental proxy variable from a partial perspective, instead of comprehensive environmental performance.…”
Section: Introductionmentioning
confidence: 80%
“…Some studies found that the implementation of the BRI has a strong policy effect, which can effectively enhance the positive impact of China's OFDI on the environments of host countries [5,29]. Additionally, the economic scale effects and industrial structure effects of China's OFDI have increased the carbon emissions of BRI countries [11]. The production technology effect has inhibited the carbon emissions of BRI countries and played a leading role [11].…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations